Teachers' Perceptions and Challenges: Evaluating TOEFL Training in an Islamic Boarding School: English - Radina Anggun Nurisma; Dias Agata; Eny Kusumawati; Irwan Sumarsono; Imam Dui Agusalim; Aris Bahari Rizki (JOEY: Journal of English Ibrahimy, 2026)
In response to the growing importance of English language proficiency in professional contexts, teacher training for widely used standardized proficiency test such as Test of English as a Foreign Language (TOEFL) has become increasingly essential. Despite the growing number of training, there remains limited understanding of how teachers perceive these programs and what challenges they face in applying the training outcomes to their daily practices. This study aimed to examine teachers’ perceptions of a TOEFL preparation training program and the challenges they encountered in applying its outcomes. An explanatory mixed-methods design was employed, involving 40 teachers from elementary, junior high, and high school levels at an Islamic boarding school in Indonesia. Quantitative data on teachers’ perceptions of the training program and qualitative data on the challenges they experienced were collected through a questionnaire combining closed- and open-ended items. The quantitative data were analyzed descriptively to illustrate the levels of teachers’ knowledge and perceptions, while the qualitative data were analyzed using a thematic approach. The findings revealed that teachers generally held positive perceptions toward the TOEFL preparation training program. However, several challenges emerged in applying the training outcomes, including institutional and environmental challenges, teacher-related challenges, and issues of professional development and sustainability.